2018
DOI: 10.1029/2017jd027823
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fire Radiative Power Estimates From VIIRS and MODIS Observations

Abstract: Satellite‐based active fire data are a viable tool to understand the role of global fires in the biosphere and atmosphere. The Moderate Resolution Imaging Spectroradiometer (MODIS) sensors on Aqua and Terra satellites are nearing the end of their lives. The Visible Infrared Imaging Radiometer Suite (VIIRS) sensor on the Suomi National Polar‐orbiting Partnership satellite and the subsequent Joint Polar Satellite System series is expected to extend the MODIS active fire record. Thus, understanding the similariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 45 publications
3
63
0
Order By: Relevance
“…Actively burning fires are detected by exploiting the strong emission of middle and thermal-infrared radiation from fires at 4-and 11-μm bands (Giglio et al, 2003;Wooster et al, 2003). The MODIS C6 active fire detection algorithm can detect active fires covering as little as 10 −3 to 10 −4 of a fire pixel (1 km × 1 km) when fire temperature is 1,000 k or higher (Giglio et al, 2003(Giglio et al, , 2016, and capture FRP as low as 2.5 MW at the nadir (Li, Zhang, Kondragunta, & Csiszar, 2018). The products also include a fire mask that classifies each pixel of a 5-min MODIS granule into one of eight categories: not processed, nonfire water, cloud, nonfire land, unknown, low confidence fire (0%-30%), nominal confidence fire (30%-80%), and high confidence fire (80%-100%; Giglio et al, 2016).…”
Section: Fire Radiative Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Actively burning fires are detected by exploiting the strong emission of middle and thermal-infrared radiation from fires at 4-and 11-μm bands (Giglio et al, 2003;Wooster et al, 2003). The MODIS C6 active fire detection algorithm can detect active fires covering as little as 10 −3 to 10 −4 of a fire pixel (1 km × 1 km) when fire temperature is 1,000 k or higher (Giglio et al, 2003(Giglio et al, , 2016, and capture FRP as low as 2.5 MW at the nadir (Li, Zhang, Kondragunta, & Csiszar, 2018). The products also include a fire mask that classifies each pixel of a 5-min MODIS granule into one of eight categories: not processed, nonfire water, cloud, nonfire land, unknown, low confidence fire (0%-30%), nominal confidence fire (30%-80%), and high confidence fire (80%-100%; Giglio et al, 2016).…”
Section: Fire Radiative Powermentioning
confidence: 99%
“…In addition, due to the MODIS "bow-tie effect" (adjacent scans overlap each other at off-nadir; Wolfe et al, 2002), the same fire in the offnadir region may be observed twice or even more times (Freeborn et al, 2014;Peterson et al, 2013). Therefore, the interscan duplicated fire detections were corrected following the method proposed in a previous study (Li, Zhang, Kondragunta, & Csiszar, 2018). The corrected MODIS daytime FRP is simply referred to as the FRP hereafter.…”
Section: Fire Radiative Powermentioning
confidence: 99%
“…Even so, VIIRS would not be able detect fires obscured by haze and clouds and those outside of its overpass time. Li et al (2018) showed that even slight differences in VIIRS and MODIS/Aqua overpasses of ∼15 min can lead to large discrepancies in active fire detections over Punjab. In addition, cloud cover and increasing haziness, indicated by AOD, can limit retrieved scenes that are usable and block active fires from satellite detection .…”
Section: Ignitionsmentioning
confidence: 99%
“…Our goal has been to provide an introduction to this special issue and to provide a review of current fire‐smoke emissions characterization, data, and modeling. There are several dominating themes that permeate this special issue and review that include the linkages and dependency of outcomes on ecosystem fuels (Desservettaz et al, ; Gomez et al, ; H Lee et al, ; X Liu et al, ; Petrenko et al, , all this issue) and the interdependencies between the terrestrial, atmosphere, and climate domains (e.g., fuels, fire weather, detrainment and transport, chemistry, deposition of smoke, impacts on radiation, and precipitation; Antokhin et al, ; Bluvshtein et al, ; Kalashnikova et al, ; F. Li, et al, ; Lu & Sokolik, ; Souri et al, ; Wang et al, ; Zhu et al, , all this issue). The ultimate purpose of understanding fire‐smoke emissions, their properties, transport, and atmospheric impacts is twofold: to clarify chemistry and transport to improve air quality and health and to accurately integrate and model feedback within climatic systems.…”
Section: Summary and Recommendationsmentioning
confidence: 99%